2020
DOI: 10.3390/agriculture10030088
|View full text |Cite
|
Sign up to set email alerts
|

Land Equivalent Ratio in the Intercropping of Cucumber with Lettuce as a Function of Cucumber Population Density

Abstract: Lettuce and cucumber are two important vegetables cultivated in greenhouses. Intercropping can increase the yield without increasing the demands for inputs. A more efficient use of resources in production systems can reduce costs and environmental impacts. We evaluated the land equivalent ratio (LER) of intercropping cucumber and lettuce as a function of the cucumber population. An experiment was conducted in a greenhouse to evaluate the cucumber population density (100, 85, 70, and 55% of 2.35 plants m−2) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Hendges et al (2019), evaluating an intercrop of kale with the Apiaceae, coriander and parsley, also used in the intercrops grown in this study and under similar growing conditions, found that crops of this family afforded the highest values for LER, indicating greater biological efficiency. This result shows that the intercropped system favoured growth and production in the vegetables, which means that the combinations used were viable (Ribas et al, 2020).…”
Section: Biological Efficiency Of the Systemmentioning
confidence: 74%
“…Hendges et al (2019), evaluating an intercrop of kale with the Apiaceae, coriander and parsley, also used in the intercrops grown in this study and under similar growing conditions, found that crops of this family afforded the highest values for LER, indicating greater biological efficiency. This result shows that the intercropped system favoured growth and production in the vegetables, which means that the combinations used were viable (Ribas et al, 2020).…”
Section: Biological Efficiency Of the Systemmentioning
confidence: 74%
“…the balance between what is produced inside the chloroplasts and what is consumed by the respiratory process (Peixoto et al, 2011;Pedò et al, 2014), indicated similar photosynthetic efficiency in plants grown under both cropping systems in each cycle. This performance can be explained by the regular interception of radiation by the plants (Ribas et al, 2020). Such a result shows that the population density used for single crops and for the intercropping systems with arugula was adequate and did not cause competition among the plants, at least in terms of luminosity.…”
Section: Journal Of Agricultural Studiesmentioning
confidence: 78%
“…Such competition is better understood from physiological evaluations of gas exchange and leaf area that can demonstrate competitive ability above the ground as a function of the luminous environment. This can also happen through the observation of various indices that evaluate the individual performance of the intercropped species in relation to its behaviour as a single crop and/or in relation to the other intercropped species (Batista et al, 2016;Ribas et al, 2020). These indices allow the degree of competitiveness between crops to be quantified, and their aggressivity and dominance in the system, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The lettuce yield reduction and plant development was affected by limitations on growth in the intercropping system. The shade of cucumber plants reduced the passage of solar radiation and consequently, the photosynthetic activity, in lettuce in the intercropping system (Ribas et al, 2020).…”
Section: Journal Of Agricultural Studiesmentioning
confidence: 98%
“…Several studies have shown positive effects on the intercropping of lettuce with other vegetables, showing agronomic viability. As an example, some studies confirmed the potential for intercropping lettuce and cucumber (Silva et al, 2008); lettuce and onion (Paula et al, 2009;Haan and Vasseur, 2014); lettuce and marcela (Mota et al, 2011); lettuce and broccoli (Ohse et al, 2012), beans, okra, lettuce and pumpkin (Hadidi et al, 2011), corn andpumpkin (Mandumbu andCaravina, 2012), broccoli and lettuce (Yildirim and Turan, 2013) and lettuce and cucumber (Ribas et al, 2020).…”
Section: Introductionmentioning
confidence: 94%